2018
DOI: 10.1007/s00268-018-4526-9
|View full text |Cite
|
Sign up to set email alerts
|

Early Consequences of Pectus Excavatum Surgery on Self‐Esteem and General Quality of Life

Abstract: BackgroundAn early observation after chest wall correction is direct inspection from the PE patient of their “new” thorax. Changes in self-perception may give raise to other psychological adaptations. The aim of this study was to evaluate the early changes in the fields of self-esteem, body image and QoL.MethodsProspective observational longitudinal multicenter cohort study. Self-esteem, emotional limitations and general health were assessed using the Child Health Questionnaire (CHQ) in patients under 18 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 32 publications
0
19
0
5
Order By: Relevance
“…[13][14][15] A new multicenter study from the Netherlands showed improved body image, increased self-esteem, and increased psychological resilience after MIRPE, with the most marked change reported in the first 6 weeks after surgery. 8 Steinmann et al included in their prospective study patients with PE and PC who underwent surgical correction and found among this group a highly disturbed preoperative body image with reduced mental QoL and low self-esteem that differed significantly from the control group. 1 The literature for QoL following correction of PC remains limited.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] A new multicenter study from the Netherlands showed improved body image, increased self-esteem, and increased psychological resilience after MIRPE, with the most marked change reported in the first 6 weeks after surgery. 8 Steinmann et al included in their prospective study patients with PE and PC who underwent surgical correction and found among this group a highly disturbed preoperative body image with reduced mental QoL and low self-esteem that differed significantly from the control group. 1 The literature for QoL following correction of PC remains limited.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Postoperatively, many studies showed significantly improved body image and self-esteem among patients, which has a substantial impact on their QoL. [1][2][3][4][5][6][7][8] In this review, we evaluate all published studies on body image, self-esteem, or QoL in patients with pectus excavatum (PE) and pectus carinatum (PC).…”
Section: Introductionmentioning
confidence: 99%
“…Голландські автори успішно застосовували як пацієнт-контрольовану епідуральну аналгезію, так і пацієнт-контрольовану внутрішньовенну аналгезію морфіном, інколи з додаванням кетаміну у пацієнтів з ЛДГК після корекції за Nuss протягом перших трьох діб після операції, з подальшим переходом на пероральний прийом аналгетиків [13].…”
Section: обговорення результатівunclassified
“…Patients with a PE show a lower self-esteem compared with their peers influencing their development during adolescence and thereafter. 2 Physical complaints, such as localized rib or sternum pains, may also influence their social behavior. Unfortunately, Introduction Pectus excavatum (PE) is the most common deformity of the anterior chest wall and can be corrected surgically with different techniques.…”
Section: Introductionmentioning
confidence: 99%